Program Sekolah Ramah Anak Sebagai Upaya Mencegah Perilaku Bullying pada Sekolah-Sekolah di Kabupaten Madiun - Oktavia Dea Apriningrum, Cindy (TAZKIA JURNAL, 2025)
This study aims to determine: (1) explain the preconditions of the emergence of the child-friendly school program (CFS); (2) describe students' bullying behavior; (3) describe the implementation of the CFS program to prevent bullying behavior; (4) examine and analyze the needs of students and teachers in the formulation of CFS to prevent bullying behavior in schools, and; (5) formulating the construction of child-friendly schools according to need analysis and implementation of CFS program. This study used a quantitative study with a comparative etnografi strategy. Data collection focuses on deep interview, participant observation, focus groups discussion, and questionaire. The interactive analysis developed by Miles, Hubberman, and Saldhana use in this study. There are five significant findings from this study : (1) the precondition of child-friendly school programs is top-down bureaucratic instructions due to Child Friendly City Policies. (2) bullying behavior find in schools in the form ofverbal, face-to-face bullying and distribute to social media with majority female students as victims who have seniority relationships (3) there are three different responses in each school amid applying SRA such as innovative-initiative, adaptive, and passive. (4) student needs for bullying prevention through SRA are more centered on creating school conditions that are safe, comfortable and free from violence, and thereare three focusesof school needs in bullying prevention like assistance and sustainability, second technical implementation, and third evaluation mechanism. (5) Piaget's knowledge construction had main role in the SRA construction in schools. This also affects how each school seeks to prevent bullying through various activities for students.